The 13th Conference of the International Sports Engineering Association 2020
DOI: 10.3390/proceedings2020049017
|View full text |Cite
|
Sign up to set email alerts
|

Sprint and Change of Direction Performances on Three Different Futsal Playing Surfaces

Abstract: This study was conducted to clarify the differences in sprint and change of direction performances on different futsal flooring systems (area-elastic (AE) vs. combined-elastic (CE)). Eight recreational athletes were recruited to perform the 505-agility test on three different EN 14904-certified futsal playing surfaces (AE, CE1 and CE2). All participants wore an identical footwear during the test. Timing-gate systems were utilized to record the time of 5-m sprint run-up and the change of direction components fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…When some studies in the literature, which are similar to the subject of our study, are examined; In a study conducted by Ayarra et al, (2018) on futsal players in Spain, 505 agility test values were found to be 2.29±0.09 seconds in 2nd League players, 2.26±0.08 seconds in 3rd League players, and 2.33±0.15 seconds in Junior category players. Yanci et al, (2017) conducted a study with 44 futsal players with a mean age of 22.5±5.0 years, and the test values of the athletes were 2.28±0.09 seconds; Ismail et al, (2020) found the test values of 2.57 seconds. In the study conducted by Andraši´c et al, (2021), it was found that 2.15±0.17 sec.…”
Section: Discussionmentioning
confidence: 99%
“…When some studies in the literature, which are similar to the subject of our study, are examined; In a study conducted by Ayarra et al, (2018) on futsal players in Spain, 505 agility test values were found to be 2.29±0.09 seconds in 2nd League players, 2.26±0.08 seconds in 3rd League players, and 2.33±0.15 seconds in Junior category players. Yanci et al, (2017) conducted a study with 44 futsal players with a mean age of 22.5±5.0 years, and the test values of the athletes were 2.28±0.09 seconds; Ismail et al, (2020) found the test values of 2.57 seconds. In the study conducted by Andraši´c et al, (2021), it was found that 2.15±0.17 sec.…”
Section: Discussionmentioning
confidence: 99%
“…In performance aspect, previous studies have investigated the effect of the playing surface in tennis (Cui et al, 2019), rugby (Ballal et al, 2014), ice hockey (Fortier et al, 2014), American football (Kent et al, 2015), squash (Chapman et al, 1991), dancing (Reeve et al, 2013), basketball and gymnastics (Bressel et al, 2007). In indoor sports, some common types of training and playing surfaces are wooden and synthetic (or artificial) floors (Ismail et al, 2020;Pasanen et al, 2008;, generally offering lower and higher available friction, respectively. In futsal, the playing surface was reported to have an effect on the time required to complete a change-of-direction task and this agility performance has been taken as a key indicator of the performance level of futsal players (Sekulic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%